Soybean breeding effects on seed yield determination under contrasting water supply - Avalos Britez, Selva Rocío; Di Mauro, Guido; Abdala, Lucas J.; Otegui, María Elena (Scilight, 2025)
Soybean seed yield (SY) gains have been achieved through both genetic improvement and advances in agronomic practices. However, the contribution of genetic gain (GG) to overall yield improvement can vary depending on specific environmental conditions, particularly under contrasting water supply. In this study, we analyze the impact of traditional soybean breeding on SY, its physiological determinants, and numeric yield components across contrasting water supply conditions. Field trials included a representative set of widely adopted commercial varieties from maturity groups (MGs) IV–V released between 1982 and 2016, grown in the core production zone of the humid Pampas region in Argentina. Results showed a biphasic GG trend for SY, which declined at a rate of 0.64% year⁻1 until 2004 and increased at 1.9% year⁻1 from 2004 onwards. These trends were mirrored by changes in harvest index (HI) and, to a lesser extent, by aboveground biomass (BT), particularly under water-limited conditions. Changes in BT were reflected in similar trends in radiation and water use efficiencies, as no significant breeding effects were observed on resource capture. The most consistent effects of breeding were observed on seed number and pod number, with no clear trends in individual seed weight. The absence of differences in crop evapotranspiration among genotypes suggests that recent genetic progress improved the efficiency of biomass production rather than increasing water use. This study highlights the importance of analyzing GG within specific MGs and environments, revealing previously undetected shifts in SY trends within MG IV–V adapted to humid temperate regions.